Effect of Nano Urea Liquid Fertilizer Application in Paddy under Different Agroclimatic Zones of Odisha, India - , Rahul Dev Behera; , P. Majhi; , S. Dash; , P. J. Mishra; , J. Sen; , A. Phonglosa; , Ipsita Das; , S. Priyadarshini; , N. C. Barik; , S. Sahu; , S. Biswal (Archives of Current Research International, 2025)
A field experiment was conducted in the three agroclimatic zones of Odisha located in East & South coastal plain regions (Jagatsinghpur), North Eastern coastal plain regions (Jajpur) & Western central table land regions (Bargarh) of Odisha to study the nano urea effect on transplanted rice by taking three treatments on 100 per cent NPK, 50 per cent N + 100 pec cent PK +Nano urea and 75 per cent N + 100 pec cent PK +Nano urea with seven replications in the RBD design. From the above experiment we conclude that the effect of nano urea increases the plant height at different stages of transplanted rice. The 75 per cent recommended N with 100 per cent PK and two sprays of nano urea @ 0.4 per cent at tillering & PI stages increases plant height at active tillering, panicle initiation, flowering, maturity stages in almost similar with application of 100 per cent NPK at Bargarh, Jagatsinghpur & Jajpur district of Odisha. Similarly the average yield was recorded almost nearer to similar in both the 100 per cent NPK with nano urea + 75 per cent N + 100 per cent PK. The farmer's net revenue per hectare is increased by applying nano urea twice with 75% less urea. This also reduces the 25% urea application, which is good for managing soil health. So, the nano urea application is better and can be recommended to the farmers to minimize the chemical urea application and efficient use of nitrogen to the paddy for better crop growth, development & increasing yield.